Trace element geochemistry of sphalerite and chalcopyrite in arc-hosted VMS deposits - Torró, L.; Benites, D.; Vallance, J.; Laurent, O.; Ortiz-Benavente, B.A.; Chelle-Michou, C.; Proenza, J.A.; Fontboté, L. (Elsevier, 2022)
Trace element compositions of sphalerite and chalcopyrite have been investigated for four arc-hosted Cretaceous VMS deposits (María Teresa, Perubar, and Palma in Peru, and Cerro de Maimón in the Dominican Republic) using laser ablation inductively-coupled plasma mass spectrometry. In sphalerite, Fe, Mn, Cd, Hg, Ag, Sb, Se, In, Ge, and Ga are lattice-bound, whereas Sn, Tl, Bi, and Pb occur at least partly as mineral microinclusions. Significant variations in the contents of minor and trace elements are observed in sphalerite grains from individual deposits. A strong negative correlation between Fe (Inter-Quartile Range [IQR] 44,009–18,168 ppm) and Zn indicates a dominant Fe2+ ↔ Zn2+ simple isovalent substitution. Regarding potential high-tech by-products, the contents of In (IQR 42–1.6 ppm, up to 415 ppm) and Ga (IQR 31–5.9 ppm, up to 96 ppm) in the studied sphalerite are normally much higher than those of Ge (IQR 0.85–0.16 ppm, up to 9.3 ppm). Correlation trends suggest Cu+ + In3+ ↔ 2Zn2+, Cu+ + Ga3+ ↔ 2Zn2+, and more complex substitution mechanisms of Zn involving combinations of monovalent (Cu+, Ag+), divalent (Ge2+?), trivalent (In3+, Ga3+, [Sn3+?]), and quadrivalent (Ge4+, Sn4+) cations. As for chalcopyrite, Zn, Ag, Sn, Cd, Se, In, Ga, and Ge are interpreted to be lattice-bound, whereas Mo, Au, Tl, Sb, Pb, and Bi probably occur as microinclusions. Relative to sphalerite, chalcopyrite is depleted in In (IQR 28–8.4 ppm, up to 49 ppm) and Ga (IQR 8.3–2.9 ppm, up to 24 ppm) and enriched in Ge (IQR 5.9–0.70 ppm, up to 80 ppm). Of the other trace elements, Zn (IQR 426–190 ppm) is the most highly concentrated in the studied chalcopyrite, followed by Ag (IQR 136–23 ppm), Se (IQR 64–22 ppm), Sn (IQR 53–1.3 ppm), and Cd (IQR 12–6.0 ppm). General positive correlation trends between Zn, Cd, In, Ge, and Ga in chalcopyrite suggest varied coupled substitution mechanisms of Fe and Cu with fluctuating valences due to covalent bonding. Trace-element distribution patterns in sphalerite and chalcopyrite were studied for the zone-refined Sofía-D massive sulfide body in the María Teresa deposit, which comprises a lower lower portion of dominant pyrite sheathed upward by zones of chalcopyrite (Cu zone), sphalerite (Zn zone) and galena + sphalerite ± fahlore ± barite (Pb – Zn – Ag zone). Bottom to top of the sulfide body, sphalerite records progressive depletion in In, Cu, Mn, and Se, and enrichment in Ge. This distribution pattern agrees with increasing crystallization temperatures and/or volatile magmatic influx towards the lower portion of the massive mineralization. Distribution of trace elements in chalcopyrite is rather uneven except for a sustained enrichment in Se towards the basal portion of the sulfide body. The fact that such trends are preserved in spite of extensive recrystallization during thermal metamorphism in parts of the Sofía-D massive sulfide mineralization suggests i) a closed metamorphic system and ii) that element interdiffusion was prominently local. Accordingly, we propose that sphalerite lattice-bound trace elements distribution patterns described in this article can help determine the polarity of massive sulfide bodies in VMS districts in metamorphosed and tectonized terranes.
Keywords: Volcanogenic Massive Sulfide (VMS) deposits; Sphalerite; Chalcopyrite; Minor and trace elements; https://purl.org/pe-repo/ocde/ford#1.05.02